(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the present study was to evaluate the root canal morphology of the maxillary and mandibular canines using cone-beam computed tomography (CBCT) in a Turkish population.Material and Methods: CBCT images of 377 maxillary and 419 mandibular canines were examined. The number of roots and their morphology, number of canals per root and canal configurations according to the Vertucci’s classification were recorded. Canal configurations and presence or absence of lateral canals were examined regarding gender, age groups, and tooth side. Anatomic symmetry in canal morphology of bilateral canines was also recorded. The data were evaluated by Pearson Chi-square test (p .05). Results:The prevalence of type I canal configuration in maxillary and mandibular canines was 96.3% and 87.8%, respectively. Twenty-one percent of the maxillary canines and 14.8% of the mandibular canines had accessory canals. In maxillary canines, no significant difference was observed in the prevalence of accessory canals between males and females and between age groups. In mandibular canines, lateral canals and complex canal morphology were detected significantly more often in females. Prevalence of complex root canal increased with age in both maxillary and mandibular canines and great anatomic symmetry was observed in canal morphology of bilaterally present teeth in the same patient.Conclusion: CBCT is a useful tool for evaluation of root and canal morphology. Our results can provide valuable aids for clinicians during root canal treatment of canines.